Accounting for decision making and control - Zimmerman, Jerold L., 1947- (Boston : McGraw-Hill Irwin, 2009)
Accounting for Decision Making and Control provides students and managers with an understanding and appreciation of the strengths and limitations of an organization's accounting system which allows them to be more intelligent users of these systems. The 6th edition provides a framework for thinking about accounting systems and a basis for analyzing proposed changes to these systems. The text demonstrates that managerial accounting is an integral part of the firm's organizational architecture, not just an isolated set of computational topics. This new edition has improved its readability and accessibility to students.
Chapter 1: Introduction Chapter 2: The nature of costs Chapter 3: Opportunity cost of capital and capital budgeting Chapter 4: Organizational architecture Chapter 5: Responsibility accounting and transfer pricing Chapter 6: Budgets and budgeting Chapter 7: Cost allocation: Theory Chapter 8: Cost allocation: Practices Chapter 9: Absorption cost system Chapter 10: Criticisms of absorption cost systems: Incentives to overproduce Chapter 11: Criticisms of absorption cost systems: Inaccurate product costs Chapter 12: Standard costs: Direct labor and materials Chapter 13: Overhead and marketing variances Chapter 14: Management accounting in a changing environment
Includes bibliographical references and index.
Keywords: Managerial accounting